Juridical Analysis of the Implementation of Handover of Housing Infrastructure, Facilities and Utilities - Febrianti Dwi Puspaningrum; Suhadi Suhadi (Faculty of Law, Universitas Negeri Semarang, 2024)
Infrastructure, Facilities and Utilities are the basic physical equipment of a residential environment that meets certain standards for the needs of a decent residence. Providing and handing over Infrastructure, Facilities and Utilities is an obligation that the developer must fulfill when building housing. However, in Tangerang City, there are still many developers who have not handed over the Infrastructure, Facilities and Utilities even though the time period has passed, resulting in the abandonment of the Infrastructure, Facilities and Utilities. This research uses empirical juridical methods with a qualitative approach. Data collection techniques in this research used observation, interview and documentation techniques. The results of this research indicate that the inhibiting factor in handing over housing Infrastructure, Facilities and Utilities by developers to the government in Tangerang City is the abandonment of Infrastructure, Facilities and Utilities by developers whose whereabouts are unknown. Infrastructure, Facilities and Utilities that have not been handed over are managed entirely by the Developer, so that if the Developer's whereabouts cannot be known then the management of the Infrastructure, Facilities and Utilities will not work which will result in the abandonment.